FLORISTICS AND STRUCTURE OF A LOWLAND DIPTEROCARP FOREST AT WANARISET SAMBOJA, EAST KALIMANTAN, INDONESIA - Kartawinata, Kuswata -; -, PURWANINGSIH -; Partomihardjo, Tukirin -; Yusuf, Razali -; Abdulhadi, Rochadi -; Riswan, Soedarsono - (Research Center for Biology, 2008)
KARTAWINATA, K., PURWANINGSIH, PARTOMIHARDJO, T., YUSUF, R., ABDULHADI, R. & RISWAN,S. 2008.Floristics and structure of a lowland dipterocarp forest at Wanariset Samboja, East Kalimantan, Indonesia.Reinwardtia 12(4): 301â 323. â The results of a floristic inventory of trees with DBH < 10 cm in a lowland dipterocarp forest in East Kalimantan show that 553 species of 192 genera in 62 families, represented by 5847 individuals, with the total basal 2 area of 350.01 m occurred in the plot of 10.5 hectare sampled. The two leading families in terms of number of species were Myrtaceae and Lauraceae while according to the total sum of importance values for families were Dipterocarpaceae and Euphorbiaceae. The forest had the second highest species richness in Indonesia. We recorded 225 species of dipterocarps , constituting 4.53 % of total species with basal area of 85.53 m . or 24.44 % of the total basal area in the plot. Shorea laevis (a diptererocarp) and Pholidocarpus majadum, (a palm) were the most prominent species occurring here and were two of the ten leading species. The species-area curve rose steadily even up to an area of 10.5 hectare, with a very slight indication of levelling off at about five hectares, indicating high heterogeneity of the forest. Three largest trees were Shorea pauciflora (DBH = 196.50 cm) Dipterocarpus cornutus (DBH = 170.90 cm), and Alstonia scholaris (DBH = 170.00 cm) , Some species could be identified as fruit trees and medicinal plants.